Histopathologic and Flow-Cytometric Analysis of Neoplastic and Benign “background” Tissue in Breast Carcinoma Resections - Daniel W. Visscher; Debra S. Gingrich; Carmen Leon-Armin; Pamela Tabaczka; John D. Crissman (Analytical Cellular Pathology)
Two-color, multiparametric synthesis phase fraction (SPF) analysis of cytokeratin-labeled epithelial cells was flow cytometrically performed on both benign (SPFb) and malignant tissue samples (if available, SPFt) from 132 mastectomy/lumpectomy specimens. These data were then correlated with clinicopathologic features, including (1) tumor differentiation, (2) the proportion of tumor comprised of duct carcinoma-in situ (DCIS), and (3) the histology of accompanying benign breast tissue, classified by predominant microscopic pattern as intact, normal terminal duct lobular units (NTDLU, 34% of cases), atrophic (AT, 33% of cases), proliferative fibrocystic (PFC, 26% of cases), and non-proliferative fibrocystic (NPFC, 7% of cases). SPFt was inversely correlated with extent of DCIS (DCIS =0 – 20% tumor volume – 12.7% mean SPFt, vs. DCIS >20% tumor volume – 6.4% mean SPFt, p = 0.001). SPFt also correlated with the histology of background benign breast tissue (NTDLU – 14.8% mean SPFt vs. AT – 6.9% mean SPFt vs. PFC – 12.7% mean SPFt, p = 0.05) but it did not correlate with patient age or SPFb (overall mean =0.73%). SPFb was correlated with patient age (>56 yr – 0.59% mean SPFb vs. < yr – 0.84% mean SPFb, p = 0.02), with background histology (NTDLU – 1.1% mean SPFb vs. AT – 0.43% mean SPFb vs. PFC – 0.70% mean SPFb, p < 0.02) and with the grade of the neoplasm (well/moderate – 0.58% mean vs. poorly differentiated – 0.85% mean, p = 0.04). Patients having a background of PFC were significantly older than patients with a background of NTDLU (45.2 yr vs. 60.2 yr, p = 0.01).